Clinical utility of stimulated cholescintigraphy using a standardized Ensure‐Plus fatty meal protocol in patients with suspected functional gallbladder disorder: a retrospective study of seven‐years clinical experience. Issue 4 (30th November 2021) - Li, Acrane Y.; Yue, Helen; Kavnoudias, Helen; Cherk, Martin H.; Nadebaum, David P.; Barton, Howard; Beech, Paul; Yap, Kenneth S. K.; Smith, Marty; Paul, Eldho; Barber, Thomas W.
ABSTRACT: Background: The clinical utility of fatty meal stimulated cholescintigraphy particularly using a standardized formulation in patients with suspected functional gallbladder disorder has not been extensively studied. We present our seven‐year clinical experience using an Ensure plus protocol. Methods: A retrospective study was performed on patients undergoing stimulated cholescintigraphy using Ensure Plus for evaluation of suspected functional gallbladder disorder. A gallbladder ejection fraction (GBEF) of <33% was considered abnormal. Results: Of the 173 patients evaluated, 57 (33%) had an abnormal GBEF, 112 (65%) had a normal GBEF and 4 (2%) had no gallbladder visualization. Of the 57 patients with an abnormal GBEF, symptom improvement occurred in 30/31 (97%) who underwent cholecystectomy and in 17/26 (65%) who were managed conservatively ( p  = 0.003). Of the 112 patients with a normal GBEF, symptom improvement occurred in 8/10 (80%) who underwent cholecystectomy and 74/102 (73%) who were managed conservatively ( p  = 1.000). In the subgroup of 102 patients with a normal GBEF managed conservatively, those without symptomatic improvement had lower GBEFs compared to those with symptomatic improvement (median GBEF 46% versus 57%, p  = 0.019). Conclusion: Our retrospective results support a clinical role for stimulated cholescintigraphy using Ensure Plus in the evaluation of patients with suspected functional gallbladder disorder. While an abnormal GBEF predicts good surgical outcome, our results suggest that using an absolute GBEF cut off value of <33% may not apply to all patients and hence GBEF results should only be used as an adjunct in the surgical decision‐making process. Abstract : Retrospective study assessing 173 patients that underwent Ensure‐plus stimulated cholescintigraphy for functional gallbladder disorder. We found this imaging investigation offers important supportive value to the clinical decision making process, in particular, identifying patients who can benefit from cholecystectomy.